Bioactive secondary metabolites from the leaves of Secamone africana (Olive.) Bullock - Sekandi, Peter; Namukobe, Jane; Byamukama, Robert; Akala, Hoseah M.; Yeda, Redemptah A.; Heydenreich, Matthias (International Journal of Biological and Chemical Sciences, 2020)
Secamone africana leaves are used in the treatment of malaria and other ailments in Uganda. The aim of the study was to characterize the antiplasmodial compounds from the leaves of Secamone africana. The leaves were extracted sequentially using dichloromethane (DCM) and methanol (MeOH). The crude extracts and isolated compounds were evaluated for their antiplasmodial activity against the chloroquine sensitive Sierraleone I (D6) and chloroquine-resistant Indochina I (W2) strains of Plasmodium falciparum. Isolation and purification were done using chromatographic techniques including column chromatography and high performance liquid chromatography. The isolated compounds were characterized using spectroscopic methods. The MeOH extract (IC50 = 5.45 μg/mL) was found to be more active than the DCM extract (IC50= 15.93 μg/mL) against the D6 malaria parasite. Chemical investigation of the MeOH extract yielded one new compound; 2-(2,4-dimethyloxetan-2-yl) acetic acid (3) in addition to the six known compounds; α-linolenic acid (1), conduritol B (4), β-sitosterol (5), 3,4-dihydroxybenzoic acid (6), 4-hydroxybenzoic acid (7) and coumaric acid (8). The DCM extract yielded one known compound: 1-methyl cyclobutene (2). The presence of these compounds with good anti-plasmodial activities and other bioactivities reported in literature, appears to argue for the therapeutic potential of Secamone africana.
Keywords: Secamone africana; Anti-plasmodial activity; Chromatography; Secondary metabolites